Exploring the linkages of Foreign Direct Investment in Spain since 1970’s: an ARDL approach - Cañal Fernández, Verónica; Tascón Fernández, Julio; Gómez Martín, María (Papeles de Europa, 2020)
This paper analyzes the relationship between foreign direct investment (FDI), exports and economic growth in Spain using annual time series data for the period 1970 to 2016. To examine these linkages the autoregressive distributed lag (ARDL) bounds testing approach to cointegration for the long-run is applied. The results confirm a long-run relationship among the examined variables. The Granger causality test indicates a strong unidirectional causality between FDI and exports with direction from FDI to exports. Besides, the results for the relationship between FDI and economic growth are interesting and indicate that there is no significant Granger causality from FDI to economic growth and vice-versa.
Keywords: Foreign direct investment; exports; imports; GDP; ARDL bounds; causality